DEVELOPMENT AND APPLICATION OF 1536-PLEX SINGLE NUCLEOTIDE POLYMORPHISM MARKER CHIP FOR GENOME WIDE SCANNING OF INDONESIAN RICE GERMPLASM - Dwinita W. Utami; I. Rosdianti; P. Lestari; D. Satyawan; H. Rijzaani; I M. Tasma (Indonesian Journal of Agricultural Science, 2013)
A successful molecular breeding program requires detailed and comprehensive understanding of the diversity of rice germ-plasm and genetic base of target traits. The objective of this research was to develop the high throughput 1536-SNP chip linked to heading date and yield component traits and used it for genotyping the diverse Indonesian rice germplasm. The genotype data obtained could be used for diversity analysis and genome wide association mapping study. A 1536-SNP genome wide assay was developed using the Illumina’s GoldenGate technology. The SNP markers were selected in the rice genome regions containing heading date and yield component genes or regions where the quantitative trait loci (QTLs) of the two traits were mapped. The developed custom SNP chips were then used for genotyping 467 rice accessions showing diversity in heading dates and yield components. The assay can reliably be used for diversity analysis and mapping genes associated with heading date and yield component traits. For 1536-SNP BIO-RiceOPA-1 custom chip designed, a total of 34.832 SNPs distributed in rice genome particularly in the region of heading date and yield component genes or QTLs were identified. A total of 1536-SNP were selected and confirmed to be used for genotyping analysis. Analysis performance and quality of 1536-SNP BIO-RiceOPA1 showed that 60% (918/1536) of total SNP markers had a good differentiating power in scanning the rice accessions tested (MAF > 0.2). The 1536-SNP genome wide assay Illumina’s GoldenGate designed was useful for diversity analysis and could be used as SNP marker for large scale genotyping in rice molecular breeding involving Indica-Indica, Indica-Japonica and Indica-Tropical Japonica crosses.